2016
DOI: 10.18805/ijar.11318
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphism and gene expression of chemokine receptor 6is associated with digestive disorders in rabbits

Abstract: This study aimed to investigate the possible involvement of Chemokine receptor 6 (CCR6) gene in genetic susceptibility to digestive disorders in rabbits. A total of 346 samples (161 cases vs 185 controls) were used for this case-control association study. One coding SNP (c.96C>T) spanning the CCR6 gene coding region was identified by direct sequencing and then genotyped using PCR-SSCP. The results revealed that individuals with allele "T" was significantly protective against digestive disorders (odds ratio=0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…The currently available Oryctolagus cuniculus reference genome (OryCun2.0) should be substantially improved, as it still contains many other unassembled portions and gaps that prevent, in some cases, the extraction of important genomic information derived by genome‐wide association or signature of selection studies (Ballan et al., 2022; Fontanesi et al., 2021). It is also interesting to note that none of the genes for which markers have been associated with non‐specific digestive disorders in growing rabbits of a few Chinese lines (Chen, Zhang, et al., 2013; Fu et al., 2014, 2015; Li et al., 2018; Liu et al., 2013, 2017; Yang et al., 2013; Zhang et al., 2011; Zhang, Zhang, Chen, et al., 2013; Zhang, Zhang, Peng, et al., 2013) were included or were close to the genomic regions where we identified significant or suggestively significant SNPs. These results suggest (i) that different types of disorders were considered in these previous studies or (ii) that different rabbit lines might have different genetic backgrounds that would not provide the same genetic information in association studies or (iii) that the simple candidate gene approaches that was applied in the previous studies did not have the possibility to obtain replicable results in other contexts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The currently available Oryctolagus cuniculus reference genome (OryCun2.0) should be substantially improved, as it still contains many other unassembled portions and gaps that prevent, in some cases, the extraction of important genomic information derived by genome‐wide association or signature of selection studies (Ballan et al., 2022; Fontanesi et al., 2021). It is also interesting to note that none of the genes for which markers have been associated with non‐specific digestive disorders in growing rabbits of a few Chinese lines (Chen, Zhang, et al., 2013; Fu et al., 2014, 2015; Li et al., 2018; Liu et al., 2013, 2017; Yang et al., 2013; Zhang et al., 2011; Zhang, Zhang, Chen, et al., 2013; Zhang, Zhang, Peng, et al., 2013) were included or were close to the genomic regions where we identified significant or suggestively significant SNPs. These results suggest (i) that different types of disorders were considered in these previous studies or (ii) that different rabbit lines might have different genetic backgrounds that would not provide the same genetic information in association studies or (iii) that the simple candidate gene approaches that was applied in the previous studies did not have the possibility to obtain replicable results in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence opened the possibility for the implementation of selection strategies to increase resistance against enteropathies and related pathogenic conditions in commercial meat rabbit populations and investigate the genetic factors involved in this complex pathogenic status (Garreau et al, 2008(Garreau et al, , 2012(Garreau et al, , 2021. Several studies reported that polymorphisms in candidate genes involved in host immunity might be associated with the susceptibility of non-specific digestive disorders in growing rabbits of a few lines (Chen, Zhang, et al, 2013;Fu et al, 2014Fu et al, , 2015Li et al, 2018;Liu et al, 2013Liu et al, , 2017Yang et al, 2013;Zhang et al, 2011; several genes that encode members of a family of immunoglobulin Fc receptors (FCER1G, FCRLA, FCRLB and FCGR2A) involved in the immune innate system, which might be important candidate genes for this pathogenic condition. The results obtained in this study demonstrated that resistance to an enteropathy occurring in suckling rabbits is in part genetically determined and can be dissected at the genomic level, providing DNA markers that could be used in breeding programmes to increase resistance to enteropathies in meat rabbits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ces équipes ont mis en évidence l'implication de différents gènes codant pour des récepteurs participant à la reconnaissance des pathogènes : TLR4 (« Tolllike receptor 4 » ; Zhang et al, 2011), NOD2 (« Nucleotide-binding oligomerization domain 2 » ; Zhang et al, 2013c), Dectin-1 (« Dendritic-cell associated C-type lectin 1 » ; Zhang et al, 2013b). Ils ont aussi mis en évidence les gènes suivant : MyD88 (« Myeloid differentiating factor 88 ») codant pour une protéine qui a un rôle central dans l'activation de l'immunité innée et adaptative (Chen et al, 2013) ; NLRP12 (« NLR Family Pyrin Domain Containing 12 ») qui joue un rôle dans la régulation de l'inflammation (Liu et al, 2013) ; JAK1 (« Janus Kinase ») une molécule de signalisation intracellulaire, STAT3 (« Signal transducter and activator of transcription 3 ») un facteur de transcription et de différenciation des cellules immunitaires (Fu et al, 2014) et CCR6 (« Chemokine receptor 6 ») une récepteur contrôlant le mouvement des leucocytes (Liu et al, 2017).…”
Section: Caractères De Résistance Aux Maladiesunclassified